Prácticas sociales de los grupos quiteños de Gamers World of Warcraft y League of Legends al interior de sus comunidades en el periodo 2012-2013 - Proaño Montúfar, Johanna Estefanía (2015)
This research focuses on the analysis of social practices that keep the gamer communities World of Warcraft (WoW) and League of Legends (LoL), in the city of Quito. In this work the particularities of the gamer world were established to determine the interrelationships that are generated. The characteristics of the culture of the members of the gamers communities to recognize their behavior within their social environment is also analyzed. Similarly, the causes and social consequences of belonging to a community are determined gamer. And were analyzed communication products that have emerged since the gamer communities in Quito. It took into account a cualicuatitative methodology involving gamers, family, friends and experts in different fields such as communication, sociology, psychology and education to establish a deeper structure of the subject. During the investigation, it became clear that culture and the gaming community does not have enough spaces for communication, as well as the emergence of Communications Technology and Information (TICs) to open in the world of internet. It was evident that the gamer are part of a culture that has been neglected by different sectors, but with the advancement of technology, are coming to light. Thus, this work explores the practices of the two communities and Ecuadorian gamer itself.